The grown-up's guide to teenage humans : how to decode their behavior, develop unshakable trust, and raise a respectable adult - Shipp, Josh (Harper Wave, an imprint of HarperCollins Publishers, 2017)
"In 2015, Harvard researchers found that every child who does well in the face of adversity has had at least one stable and committed relationship with a supportive adult. But Josh Shipp didn't need Harvard to know that. Once an at-risk foster kid, he was headed straight for trouble until he met the man who changed his life: Rodney, the foster parent who refused to quit on Shipp and got him to believe in himself. Now, in The Grown-Up's Guide to Teenage Humans, Shipp shows all of us how to be that caring adult in a teenager's life. Stressing the need for compassion, trust, and encouragement, he breaks down the phases of a teenage human from sixth to twelfth grade, examining the changes, goals, and mentality of teenagers at each stage" -- provided by publisher.